Dietary patterns of 5-year-old children and their correlates: findings from a multi-ethnic Asian cohort. Issue 5 (14th March 2022) - Sugianto, Ray; Wong, Shu Fang; Toh, Jia Ying; Tint, Mya Thway; Colega, Marjorelee T.; Lee, Yung Seng; Yap, Fabian Kok Peng; Shek, Lynette Pei-Chi; Tan, Kok Hian; Godfrey, Keith M.; Chong, Yap Seng; Tai, Bee Choo; et al.
Abstract: There is limited data on the dietary patterns of 5-year-old children in Asia. The study examined childhood dietary patterns and their maternal and child correlates in a multi-ethnic Asian cohort. Based on caregiver-reported 1-month quantitative FFQ of 777 children from the Growing Up in Singapore Towards healthy Outcomes cohort, cluster analysis identified two mutually exclusive clusters. Children in the 'Unhealthy' cluster (43·9 %) consumed more fries, processed meat, biscuits and ice cream, and less fish, fruits and vegetables compared with those in the 'Healthy' cluster (56·1 %). Children with mothers of lower educational attainment had twice the odds of being assigned to the 'Unhealthy' cluster (adjusted OR (95 % CI) = 2·19 (95 % CI 1·49–3·24)). Children of Malay and Indian ethnicities had higher odds of being assigned to the 'Unhealthy' cluster (adjusted OR = 25·46 (95 % CI 15·40, 42·10) and 4·03 (95 % CI 2·68–6·06), respectively), relative to Chinese ethnicity. In conclusion, this study identified two dietary patterns in children, labelled as the 'Unhealthy' and 'Healthy' clusters. Mothers' educational attainment and ethnicity were two correlates that were associated with the children's assignments to the clusters. These findings can assist in informing health promotion programmes targeted at Asian children.